2022
DOI: 10.3390/brainsci12111513
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in the Neuropathology of Bipolar Disorder: Review of Current Evidence

Abstract: (1) Background: Approximately one-third of patients with bipolar disorder (BD) do not experience sustained remission with current treatments. Presently, astrocytes, i.e., glial cells that act as key regulators of neuroinflammation, have been a target for therapeutic development. Research regarding their role in the neuropathology of BD is limited. We conducted a scoping review on evidence linking astrocytes to the pathology of BD. (2) Methods: The search was conducted in MEDLINE for studies published from ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Typically, increased YKL-40 levels in the blood are associated with the progression of multiple diseases and cancers, such as gastric cancer, colon cancer, and glioma cancer. 5 Interestingly, YKL-40 secreted from macrophages can induce cell migration and invasion of colon, gastric, and breast cancers. Therefore, sensitive and specific detection of YKL-40 in biological fluids is of great interest for clinical diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, increased YKL-40 levels in the blood are associated with the progression of multiple diseases and cancers, such as gastric cancer, colon cancer, and glioma cancer. 5 Interestingly, YKL-40 secreted from macrophages can induce cell migration and invasion of colon, gastric, and breast cancers. Therefore, sensitive and specific detection of YKL-40 in biological fluids is of great interest for clinical diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…A second biomarker examination argues for the potential importance of astrocytes in the pathophysiology of BD. Reviewing the current evidence to date, Dai et al identified several studies indicating a putative role of astrocytes in BD, with few overall studies and high heterogeneity between findings, indicating the importance of further large-scale investigations where key effect-modifying variables can be considered [ 5 ]. In terms of translation, this field could help to optimise established interventions with neuroprotective effects (including on astrocytes) such as lithium, and relevant therapies under investigation, e.g., pioglitazone, and novel targets.…”
mentioning
confidence: 99%
“…Commonly, these 10 articles contained increased sample sizes compared to older studies either through primary research studies [ 3 ], secondary analyses from multiple RCTs [ 8 ], the utilisation of large, well-defined medical records cohorts [ 9 ], or undertaking scoping reviews [ 5 , 14 , 15 ], systematic reviews and/or meta-analyses [ 6 , 7 , 12 ]. Where large samples were not justified, an innovative randomised case series approach was employed [ 13 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation